2022
DOI: 10.1093/cid/ciac673
|View full text |Cite
|
Sign up to set email alerts
|

Oral Nirmatrelvir and Ritonavir in Nonhospitalized Vaccinated Patients With Coronavirus Disease 2019

Abstract: Background Treatment of coronavirus disease-2019 (Covid-19) with nirmatrelvir plus ritonavir (NMV-r) in high-risk non-hospitalized unvaccinated patients reduced the risk of progression to severe disease. However, the potential benefits of NMV-r among vaccinated patients are unclear. Methods We conducted a comparative retrospective cohort study using the TriNetX research network. Patients ≥18 years of age who were vaccinated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
113
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(135 citation statements)
references
References 6 publications
2
113
3
Order By: Relevance
“…The antivirals approved by FDA such as Paxlovid can increase the mortality and improve adverse events in COVID-19 patients ( Wen et al, 2022 ). Paxlovid could be used in mild to moderate COVID-19 patients with high risk for progression to severe disease, but it is more suitable for immunosuppressed patients, old patients and COVID-19 patients with comorbidity, ( Ganatra et al, 2022 ; Huang et al, 2022 ; Najjar-Debbiny et al, 2022 ). Recent RCT study demonstrated that treating COVID-19 with Paxlovid led to an 89% decreased risk of progress to severe COVID-19 than the risk with placebo (Hammond et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The antivirals approved by FDA such as Paxlovid can increase the mortality and improve adverse events in COVID-19 patients ( Wen et al, 2022 ). Paxlovid could be used in mild to moderate COVID-19 patients with high risk for progression to severe disease, but it is more suitable for immunosuppressed patients, old patients and COVID-19 patients with comorbidity, ( Ganatra et al, 2022 ; Huang et al, 2022 ; Najjar-Debbiny et al, 2022 ). Recent RCT study demonstrated that treating COVID-19 with Paxlovid led to an 89% decreased risk of progress to severe COVID-19 than the risk with placebo (Hammond et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…(4) Studies that have stratified by vaccination status have identified similar relative risk reductions in vaccinated cohorts, but with smaller absolute risk reductions due to the lower baseline risk of hospitalization or death from COVID-19. (3,5,6) All previous observational studies have risks of bias including residual confounding and immortal time bias. (7) In Ontario, Canada nirmatrelvir/ritonavir became widely available, and universally funded for all patients, in the community by April 2022 with clinical criteria set by the government limiting access only to patients who were older, had comorbidities, and/or were undervaccinated.…”
Section: Introductionmentioning
confidence: 99%
“…(4) Studies that have stratified by vaccination status have identified similar relative risk reductions in vaccinated cohorts, but with smaller absolute risk reductions due to the lower baseline risk of hospitalization or death from COVID-19. (3,5,6) All previous observational studies have risks of bias including residual confounding and immortal time bias. (7)…”
Section: Introductionmentioning
confidence: 99%
“…Further viral rebound and symptom rebound have also been seen in participants who did not receive any treatment leading to viral or symptom resolution [11], imploring further investigation into this rebound phenomenon. There have been some suggestions that rebound could be related to drug pharmacodynamics [12] or anti-viral mediated interactions with viral immunologic response [13], however, peer reviewed literature on Paxlovid rebound is mostly limited to retrospective case series with wide estimates [7,9,[14][15][16]. Rebound in untreated cohorts has consisted of small prospective studies [11,17].…”
Section: Introductionmentioning
confidence: 99%